IMPLEMENTASI MODEL PEMBELAJARAN DRILL DALAM PEMBELAJARAN AL QUR’AN DI TPQ DARUL IHSAAN PADA ERA PANDEMI - Bahroin Budiya; Nuruddin Muzakki; Ainun Naafilah (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
The application of the natural drill method for learning al quran is still effectively used in learning in pandemic situations. learning during a pandemic is not much different from what was normal before the pandemic. It's just that there are schedules that have changed. The drill method has a learning sequence consisting of reciting prayers followed by the reading of Asmaul Husna. Then the students mutolaah first before mentashih their reading in front of the educator. Students are also equipped with the ability to write al-quran verses in their respective books. That way students are not only able to pronounce the al-quran correctly. But also skilled in writing the verses of the al-quran